Production of Bioethanol from Oil Palm Stumps with Varying Levels of Ammonium Sulfate ((NH₄)₂SO₄) Added through a Fermentation Process Using Tape Yeast - Ananda Braga Raihan; Heri Purwanto (RESWARA: Jurnal Riset Ilmu Teknik, 2026)
Oil palm trunk is a lignocellulosic biomass with significant potential as a raw material for bioethanol production due to its cellulose and hemicellulose content, which can be converted into fermentable sugars. This study aimed to determine the effect of ammonium sulfate ((NH₄)₂SO₄) supplementation on bioethanol production from oil palm trunk through a fermentation process using tape yeast. The research procedure included raw material preparation, hydrolysis to produce simple sugars, fermentation using tape yeast, and analysis of the resulting bioethanol content. Ammonium sulfate was used as a nitrogen source to support the growth and metabolic activity of microorganisms during fermentation. Different concentrations of ammonium sulfate were applied to obtain optimal fermentation conditions. The results showed that the addition of ammonium sulfate affected bioethanol production. Adequate nitrogen availability enhanced microbial growth, resulting in a more efficient conversion of sugars into ethanol. However, excessive nutrient addition could reduce fermentation efficiency by disrupting microbial activity. The findings indicate that oil palm trunk can be used as an alternative feedstock for bioethanol production, and that an appropriate concentration of ammonium sulfate can improve fermentation performance and increase bioethanol yield.